Bifidobacterium longum subsp. infantis CCFM1426 enhances the anti-colitic effect of vitamin A via retinoic acid restoration and gut microbiota modulation in ulcerative colitis mice - Xihua Yu; Xihua Yu; Liming Huang; Liming Huang; Yi Wang; Yi Wang; Liuruolan Li; Liuruolan Li; Wenwei Lu; Wenwei Lu; Zhijian Zhang; Hongchao Wang; et al. (Frontiers in Nutrition)
BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel disease with increasing global prevalence, making it a significant health concern. Although vitamin A (VA) plays a beneficial role in UC management, its therapeutic efficacy is limited by impaired absorption and disrupted retinoic acid (RA) metabolism. Gut microbiota are known to influence VA metabolic pathways, offering potential targets to enhance VA bioavailability and efficacy.MethodsA dextran sulphate sodium (DSS)-induced mouse model of colitis was established to evaluate the therapeutic effects of co-administering Bifidobacterium longum subsp. infantis CCFM1426 with vitamin A. Body weight, disease activity index (DAI) and colon length were monitored in mice with DSS-induced colitis. Serum levels of intestinal injury markers, inflammatory cytokines, antioxidant enzymes and colonic RA levels were measured using ELISA kits. Metagenomic analysis investigated gut microbiota composition.ResultsIt was indicated that the VA and CCFM1426 combination significantly improved colon length and DAI, enhanced serum levels of intestinal injury markers (lipopolysaccharide-binding protein, intestinal fatty acid-binding protein, diamine oxidase) and cytokines (IL-6, TNF-α, IL-10), and restored antioxidant capacity. The combination demonstrated superior efficacy in colonic RA levels and contributed to gut microbiota diversity restoration. Metabolomics analysis showed that colitis mice treated with the combination had higher levels of eicosapentaenoic acid, adenosine and anandamide.ConclusionThese findings provide novel evidence that co-administration of CCFM1426 and VA synergistically alleviates colitis by enhancing RA bioavailability through microbiota-dependent pathways.